Data from: Incorporating temporal dynamics to enhance grazing management outcomes for a long-lived species - Larios, Loralee; Hallett, Lauren (Dryad, 2022)
Identifying successful management strategies for long-lived species is
challenging, especially in fluctuating environments, because the response
of individual vital rates and overall growth rates to management action
can vary over time. A demographic approach that isolates the impact of
management and environment on individual vital rates, and assesses their
importance for growth rate over time, can indicate whether and why a
management strategy is successful. Here we take a demographic approach to
assess the success of grazing management for the perennial grass Stipa
pulchra, the state grass of California and a focus of conservation
efforts. We tracked S. pulchra populations in paired grazed and ungrazed
plots over six years, which included an historic drought and an El Niño
rain year, and calculated summary transition matrices for the main effects
of year, grazing, and year x grazing interaction for each site. We
averaged these summary transition matrices to calculate population growth
rates, l, for the main effects of year, grazing, and year x grazing and
used life table response experiment (LTRE) analysis to compare how
individual vital rates contributed to differences in l between grazed and
ungrazed plots over time. Overall we found that grazing was a successful
management strategy; grazed populations maintained a positive average
population growth rate whereas ungrazed populations declined. We found
that grazing had a larger positive effect on growth rates in wet years
than drought years. This was because grazed populations benefited from a
greater contribution of adult growth immediately following the end of the
drought compared to ungrazed populations, and from adult survival
thereafter. Synthesis and applications. Although Stipa pulchra is the
focus of many management efforts, the use of grazing for management is
contentious, and there have been few studies that take a demographic
approach to understanding S. pulchra responses over time. Our results
indicate that conservation and restoration efforts should move beyond
recruitment to focus on adult growth and survival for overall population
success. To this end, moderate grazing can be a successful strategy to
maintain S. pulchra populations and is particularly important in wet years
to promote plant growth.
Annual transition values for individual Stipa plants from 2014 through
2019 (JAppl_VC_20141516171819.csv) All values were measured for Stipa
pulchra individuals at the Vasco Caves Regional Preserve and Los Vaqueros
Watershed, Byron, CA. Please see Larios & Hallett 2022 for details
of experimental design and data collection. Column metadata secondYear =
The second year of the transition (e.g., 2015 indicates the change from
2014 to 2015) Site = The name of the grazed and ungrazed pair of
plots (Plot10, Plot15, Plot2, PlotBN, PlotBS, PlotNCow) within the Vasco
Caves Regional Preserve or Los Vaqueros Watershed. Plot10, Plot15, and
Plot2 included previously established grazing exclosures, the rest were
established at the beginning of the experiment. All grazed plots were
sheep grazed except in PlotNCow, which was cattle grazed. See Larios
& Hallett 2022 for site details Plot = The name of the plot within
a pair. G indicates a grazed plot, U indicates ungrazed Treatment =
Whether the plot was grazed or not (coded as Grazed and Ungrazed) Transect
= The transect within the plot, named by the distance in meters from the
initial transect (transect 0) Subplot = The subplot within a transect,
named by distance in meters along the transect Individ2 = A unique number
for each individual Stipa plant found within a subplot Grazer = Which type
of grazer was in the grazed treatment (coded as either Sheep or Cow) stage
= The stage class of the individual Stipa plant in the first year of the
transition (e.g., if secondYear is 2015, stage refers to the life stage in
2014). stage is coded as either seedling (when the individual was observed
as a seedling in the first year), continuous (when the individual was a
juvenile or adult in the first year), or NA (when the individual did not
appear until the second year) stageNext = The stage class of the
individual Stipa plant in the second year of the transition (e.g., the
same year as secondYear). stageNext is coded as either seedling (when the
individual was observed as a seedling in the second year), continuous
(when the individual was either a juvenile or adult), or dead (when the
individual was present in the first year but not in the second) size = The
area in cm2 of the individual Stipa plant in the first year of the
transition sizeNext = The area in cm2 of the individual Stipa plant in the
second year of the transition surv = Whether the individual survived the
transition from the first to second year, coded as a binary (0 if the
individual did not survive, 1 if it did) offspringNext = Whether the
individual was offspring that appeared in the second year of the
transition (coded as NA if the individual was present in the first year,
and sexual if the individual was a seedling in the second year) fec =
Whether the individual produced seeds in the second year, coded as a
binary (0 if the individual did not produce seeds, 1 if it did) fec1 = The
number of culms the individual produced in the second year if it produced
seeds seed = The average estimated number of seeds per culm produced for
Stipa plants within that plot pair Transition Matrices for six populations
that were either grazed or ungrazed over five transition periods from 2014
to 2019 (JAppl_Stipa Matrices_2014_2019.csv) All probabilities were
estimated from the censused data reported in the annual transition values
file entry (JAppl_VC_20141516171819.csv). Please see Larios &
Hallett 2022 for details of experimental design and data collection.
Column metadata secondYear – The second year of the transition (e.g., 2015
indicates the change from 2014 to 2015) Treatment - Whether the plot was
grazed or not (coded as Grazed and Ungrazed) Site - The name of the grazed
and ungrazed pair of plots (Plot10, Plot15, Plot2, PlotBN, PlotBS,
PlotNCow) within the Vasco Caves Regional Preserve or Los Vaqueros
Watershed. Plot10, Plot15, and Plot2 included previously established
grazing exclosures, the rest were established at the beginning of the
experiment. All grazed plots were sheep grazed except in PlotNCow, which
was cattle grazed. See Larios & Hallett 2022 for site details
sdlg_sdlg – Transition probability for seedlings staying seedlings
juv_sdlg - Transition probability for juvenile fecundity adult_sdlg -
Transition probability for adult fecundity sdlg_juv - Probability for
seedlings transitioning to juveniles juv_juv - Transition probability for
juveniles staying juveniles adult_juv - Probability for an adult to
regress to a juvenile sdlg_adult - Probability for seedlings transitioning
to adults juv_adult - Probability for juveniles transitioning to adults
adult_adult - Transition probability for adults staying adults
Keywords: FOS: Natural sciences; California grasslands; Drought; plant demography; life table response experiment (LTRE); Population growth; Stipa pulchra; rainfall variability